1993
DOI: 10.1136/bmj.306.6877.546
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis DNA in tissue affected by sarcoidosis.

Abstract: Objective-To investigate the prevalence of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
2
1

Year Published

1994
1994
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(45 citation statements)
references
References 20 publications
1
41
2
1
Order By: Relevance
“…136 Inhaled antigens have been studied, and evidence has been found for the presence of airborne typical and atypical mycobacteria. 137 Only histological examination of affected tissue, however, can confirm clinical diagnosis. 138 Intraocular sarcoidosis can present as acute or chronic uveitis, and typical signs include acute anterior uveitis, chronic anterior uveitis, intermediate uveitis, multifocal choroiditis, retinal vasculitis and optic disc swelling 139 (figure 2).…”
Section: Behçet's Diseasementioning
confidence: 99%
“…136 Inhaled antigens have been studied, and evidence has been found for the presence of airborne typical and atypical mycobacteria. 137 Only histological examination of affected tissue, however, can confirm clinical diagnosis. 138 Intraocular sarcoidosis can present as acute or chronic uveitis, and typical signs include acute anterior uveitis, chronic anterior uveitis, intermediate uveitis, multifocal choroiditis, retinal vasculitis and optic disc swelling 139 (figure 2).…”
Section: Behçet's Diseasementioning
confidence: 99%
“…The issue has been given new life by the application of molecular biology techniques. Using mycobacteria-specific primers and the polymerase chain reaction, mycobacterial deoxyribonucleic acid (DNA) molecules were identified in granulomatous tissue (lung skin or lymph node) in one study in 7 out of 16 cases, compared to 1 out of 16 normal controls, but in only 2 out of 4 tuberculosis controls [6]. A second study, by a different group, reported contradictory findings: tissue or cell samples from 16 sarcoidosis patients were compared with 13 control tissue samples, four normal bronchoalveolar lavage samples and 11 normal volunteer lavage samples.…”
Section: Aetiologymentioning
confidence: 99%
“…Various infectious agents have been suggested as being involved, of which mycobacteria seem to be the most important. Even though a considerable number of investigators have failed to detect mycobacteria in clinical samples from patients with sarcoidosis (28,33), several studies have suggested the exclusive involvement of Mycobacterium avium complex members in sarcoidosis (8,13,20,24,25), while other studies have proposed Mycobacterium tuberculosis complex to be responsible (9,22,27,29) (Table 1). Therefore, a convincing association between sarcoidosis and mycobacterial infections has yet to be established.…”
mentioning
confidence: 99%